GEOGRAPHYCAL EFFECT ON THE CYTOTOXIC ACTIVITY OF Annona muricata L. LEAVES ETHANOL EXTRACT AGAINST MCF-7 CANCER CELL - Usep Suhendar (Universitas Pakuan, 2018)
Many studies have shown the anti-cancer activities of the chemical compounds extracted from the leaves of Annona muricata or soursop plant. Cianjur and Sukabumi are quite large soursop producing area in Indonesia. This study was carried out to determine the difference of cytotoxic activity of soursop leaves ethanolic extract which were harvested from three different areas of Cianjur (I, II, III) and Sukabumi (I, II, III). The Soursop leaves were macerated with 70% ethanol using microwave assisted extraction (MAE) method. The extract was tested in vitro on breast cancer cell line MCF7 and its constituent was identified using GC-MS apparatus. The results showed that the highest cytotoxic activity with IC50 values of 9.12 µg ml-1 was determined on the extract of soursop leaves harvested from Cianjur III area. Qualitative identification of chemical constituent shows that the soursop leaves contain alkaloid, flavonoid, triterpenoid, tannin and saponin compounds. No steroid compound was detected in the extract. It can be concluded that the geographical regions affected the biochemical properties of soursop leaves.